MUSIC RELAXATION THERAPY AS A NURSING INTERVENTION FOR IMPROVING SLEEP QUALITY IN PATIENTS WITH HYPERTENSION: TERAPI RELAKSASI MUSIK SEBAGAI INTERVENSI KEPERAWATAN DALAM PERBAIKAN KUALITAS TIDUR PADA PASIEN HIPERTENSI - Velisa Fitri Dessriyanti; Mohammad Najib; Rini Ambarwati; Dhiana Setyorini (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Hypertension is a non-communicable disease that is frequently accompanied by impaired sleep quality, which may worsen health conditions due to blood pressure fluctuations and increase the risk of complications. Sleep disturbances in patients with hypertension negatively affect quality of life and delay the recovery process. One non-pharmacological approach that may improve sleep quality is music relaxation therapy. This study aimed to analyze the effectiveness of music relaxation therapy in improving sleep quality among patients with hypertension. A pre-experimental study with a one-group pretest–posttest design was conducted. The study included 47 patients with hypertension selected using a purposive sampling technique. Sleep quality was assessed before and after the intervention using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the Wilcoxon Signed Rank Test. The results demonstrated a significant improvement in sleep quality following the music relaxation therapy intervention, as indicated by reduced complaints of difficulty sleeping, decreased frequency of nocturnal awakenings, and increased sleep comfort. The Wilcoxon Signed Rank Test showed a statistically significant difference (p = 0.000; p < 0.05), indicating that music relaxation therapy significantly improved sleep quality among patients with hypertension. These findings suggest that music relaxation therapy is a safe, practical, and effective non-pharmacological nursing intervention for improving sleep quality in patients with hypertension, particularly in primary healthcare settings.